Learning Obstacles in Understanding the Pythagorean Theorem among Ninth-Grade Students - Yuce Sandra; Didi Suryadi; Dadan Dasari (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
The Pythagorean Theorem is a fundamental concept in geometry and serves as a foundation for various mathematical topics. Despite its fundamental importance in mathematics, students still have difficulty understanding and applying this theorem correctly, indicating limited conceptual understanding. This study aimed to examine the learning obstacles encountered by ninth-grade students. This qualitative descriptive study involved 32 ninth-grade students in a junior high school in Bandung. Subjects covered in this research are considered with students who have studied the Pythagorean Theorem. Data collection using tests with eight questions, interviews with questions that make clear of the answers given by students on tests, and documentation. The result found that students had obstacles in learning the Pythagorean Theorem with three main points, namely: inadequate understanding of prerequisite material; limited conceptual understanding of the Pythagorean Theorem; and difficulty in solving contextual problems. These obstacles were further classified into ontological, epistemological, and didactical obstacles based on Brousseau’s framework. This study contributes to mathematics education by showing that learning obstacles remain evident even after students have completed formal instruction on the Pythagorean Theorem. By identifying the underlying conceptual and contextual characteristics of these obstacles, the study extends current understanding of students’ post-instruction learning obstacles and offers empirical evidence to inform future instructional planning and related research